Optimization of Extraction Factors in Aerial Plantago major L. Based on RSM to TPC Levels (Journal of Fundamental and Applied Pharmaceutical Science, 2025)
Plantago major L. is known as an old medicinal plant. Some studies report that P. major has significant benefits in the world of health because of its phenolic content. Ultrasonic-assisted extraction (UAE) was chosen because it can extract faster with better yields. The best extraction conditions need to be sought to obtain optimum phenolic levels. Optimization can be done with Response Surface Methodology (RSM). This study aimed to obtain the best extraction conditions that produce optimum total phenolic levels. This study used the RSM Box-Behnken Design method. The study was conducted using 3 factors, namely the material-solvent ratio (1:5; 1:10; 1:15), ethanol-aqueous ratio (100:0; 50:50; 0:100), and extraction time (20, 40, 60) minutes, which was formulated using Design Expert 13. Total phenolic content (TPC) was measured using a UV-Vis Spectrophotometer. The analysis revealed that the quadratic polynomial model can be used to improve the extraction of P. major aerials. The best extraction conditions for TPC were a material-solvent ratio of 1:5.09; ethanol-aqueous ratio 73.27:26.73; extraction time 29.01 min, yielding a TPC value of 29.730 mg GAE/g. The experimental data were consistent with the predicted results. It demonstrates the applicability of the model and the success of the response surface methodology in optimizing the projected extraction conditions.